СOMPARATIVE ANALYSIS OF THE SOMATIC PHRASEOLOGICAL UNITS OF THE ENGLISH AND UZBEK LANGUAGES WITH THE COMPONENT “LIPS” - Hikmatxon Ziyodxon qizi Madixanova (Scholars Digest Publishing, 2023)
This article discusses peculiarities of somatic phraseological units both English and Uzbek languages and demonstrates some results of a comparative investigation of somatisms with the component “lips”. It has been paid attention to linguocultural aspects of linguistics while doing research on comparing phraseological units of the language.
Keywords: somatism, phraseological units, comparative research, lexico-semantic groups, linguoculturology, lexical unit, somatic phraseologisms, metaphor.